2010
DOI: 10.1159/000314701
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Efficacy on Human Skin in vivo Investigated by UVA-Induced Chemiluminescence Decay Analysis via Induced Chemiluminescence of Human Skin

Abstract: Background/Aims: Exogenous factors (e.g. physical: UV irradiation; or chemical: hydrogen peroxide) and endogenous metabolic processes (e.g. cellular respiration, oxidative burst, etc.) generate oxidative stress in living tissues which are in balance with enzymatic antioxidative systems and ingested antioxidants under normal conditions. These complex biological reactions are accompanied by chemiluminescence (ultraweak photon emission). However, knowledge about the chemiluminescence decay characteristics of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
(22 reference statements)
1
29
0
Order By: Relevance
“…Determining the average sum transmission in the entire UV range, the described method refers not only to UVB-induced sunburn but also to the visible and IR spectral ranges. This is of particular importance as visible and IR irradiation of the sun can also cause the formation of free radicals and skin damage [15,16,17]. As a defense system against the action of free radicals in this optical window, topical antioxidants incorporated in cosmetic formulations [18,19,20], and the systemic [21,22,23] and combined application of antioxidants [21,24,25], are advised.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the average sum transmission in the entire UV range, the described method refers not only to UVB-induced sunburn but also to the visible and IR spectral ranges. This is of particular importance as visible and IR irradiation of the sun can also cause the formation of free radicals and skin damage [15,16,17]. As a defense system against the action of free radicals in this optical window, topical antioxidants incorporated in cosmetic formulations [18,19,20], and the systemic [21,22,23] and combined application of antioxidants [21,24,25], are advised.…”
Section: Introductionmentioning
confidence: 99%
“…The skin, the largest organ of the human body, is constantly exposed to pro-oxidant environmental stresses, such as ultraviolet (UV) radiation [1,2] . Chronic exposure of the skin to pro-oxidants results in the development of oxidative damage, leading to several skin disorders, including hyperpigmentation, immunosuppression, inflammation and premature aging of the skin [2] .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The ultraweak photon emission or weak chemiluminescence is the most frequent noninvasive technique used for the measurement of oxidative stress because of its direct correlation with the oxidative metabolic processes. [29][30][31][32][33][34][35] The effect of scavengers on ultraweak photon emission was studied in human skin exposed to various types of physical (ultraviolet and ultrasonic radiation) and chemical (hydrogen peroxide, ozone, cigarette smoke) stress factors. [30][31][32][33] It has been demonstrated that topical application of ascorbic acid prior to exposure of human skin to ultraviolet radiation (UV) significantly reduced UV-induced ultraweak photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…33 More recently, a topical application of antioxidant system (tocopheryl acetate, ferulic acid, and rutin) on human skin has been shown to significantly decrease UV-induced ultraweak photon emission. 29 Hagens et al (2008) demonstrated that exposure of human skin to ozone and cigarette smoke caused an enhancement in ultraweak photon emission, whereas topical application of antioxidant (ascorbate and α-glucosylrutin) to human skin reduced ultraweak photon emission. 31 Whereas the application of ultraweak photon emission for the detection of the oxidative metabolic processes in human skin exposed to physical and chemical stress factors is widely used, the application of spontaneous ultraweak photon emission for the detection of oxidative processes in the skin the related to the normal metabolic processes, i.e., without the use of any exogenous stress factor has received less attention.…”
Section: Introductionmentioning
confidence: 99%